Identification of the KIF18A alpha-4 helix as a therapeutic target for chromosomally unstable tumor cells - Schutt, Katherine L.; Queen, Katelyn A.; Fisher, Kira; Budington, Olivia; Mao, Weifeng; Liu, Wei; Gu, Xiaohui; Xiao, Yisong; Aswad, Fred; Joseph, James; Stumpff, Jason (Frontiers in Molecular Biosciences, 2024)
The mitotic kinesin, KIF18A, is required for proliferation of cancer cells that exhibit chromosome instability (CIN), implicating it as a promising target for treatment of a subset of aggressive tumor types. Determining regions of the KIF18A protein to target for inhibition will be important for the design and optimization of effective small molecule inhibitors. In this study, we investigated the effects of mutating S284 within the alpha-4 helix of KIF18A, which was previously identified as a phosphorylated residue. Mutations in S284 cause relocalization of KIF18A from the plus-ends of spindle microtubules to the spindle poles. Furthermore, KIF18A S284 mutants display loss of KIF18A function and fail to support proliferation in CIN tumor cells. Interestingly, similar effects on KIF18A localization and function were seen after treatment of CIN cells with KIF18A inhibitory compounds that are predicted to interact with residues within the alpha-4 helix. These data implicate the KIF18A alpha-4 helix as an effective target for inhibition and demonstrate that small molecules targeting KIF18A selectively limit CIN tumor cell proliferation and result in phenotypically similar effects on mitosis at the single cell level compared to genetic perturbations.